Biomass and Carbon Uptake of Mangrove Forests Pohorua Village, Muna Regency - muhamad iksan (International Journal of Applied Biology, 2019)
Environmental conditions caused by air pollution are so large that it impacts on changes in the ecosystem that affects all aspects of human life. Climate change is caused by increasing greenhouse gases in the earth's atmosphere because the Earth's atmosphere receives more carbon than it releases. This study aims to determine the potential of biomass and carbon uptake in mangrove stems in Pohorua village, Muna Regency. The research is quantitative descriptive, sampling using the Point Center Quarted Method (PCQM) technique measured around the height of the chest height mangrove tree (DBH). Data analysis was performed using an allometric equation in which each mangrove plant has a specific gravity. Carbon uptake found in mangroves stored in the roots, stems and leaves of mangrove plants, the results of the study showed that mangroves can absorb carbon quickly.